Infracochlear approach to the petrous apex: a report of two cases: Pristop do vrha petrozne kosti pod polžem: prikaz dveh primerov - Rebolj, Janez; Milojković, Vojin; Cvetić, Goran (Acta Medico-Biotechnica, 2021)
Purpose: Presentation of the infracochlear approach to the petrous apex of the temporal bone, based on two clinical cases.Case report: Infracochlear approach to the petrous apex of the temporal bone was performed on two patients with cholesterol granuloma and plasmocytoma. The procedure was performed through the external auditory meatus, the tympanomeatal flap was raised, and the triangular/rectangular window bounded by the internal carotid artery, jugular vein, and round window of the cochlea was drilled out to the petrous apex.Conclusion: Infracochlear approach to petrous apex is a safe operating procedure that preserves the normal external auditory canal and middle ear conductive mechanism. It is the most direct and least invasive of all procedures to reach the petrous apex, and it is suitable for both drainage procedures and biopsy of lesions in the petrous apex of the temporal bone.